2016
DOI: 10.1007/s00405-016-4067-5
|View full text |Cite
|
Sign up to set email alerts
|

The evaluation of cochlear functions in Familial Mediterranean Fever

Abstract: Familial Mediterranean Fever (FMF) is a progressive disease characterized by chronic inflammation, which also has negative effects on cochlear functions and hearing levels. We investigated whether the cochlear functions and hearing levels of FMF patients were different than healthy controls and also evaluated the relationship of hearing levels with the age at diagnosis, duration without treatment, and inflammation and lipid parameters in this study. A total of 60 patients diagnosed with FMF and 48 age, gender … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 14 publications
0
3
0
Order By: Relevance
“…This may suggest that hearing impairment in FMF is due to a chronic autoinflammation process, which may, in turn, be due to a substantial amount of subclinical inflammation that persists between attacks [15]. Many pro-inflammatory cytokine secretions are increased even in the period without attacks [21]. Several experimental studies showed that several cytokines such as TNF-a, IL-1b, and IL-6, besides playing an important role in allergic disease [22], also have a critical role in damaged cochlea.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…This may suggest that hearing impairment in FMF is due to a chronic autoinflammation process, which may, in turn, be due to a substantial amount of subclinical inflammation that persists between attacks [15]. Many pro-inflammatory cytokine secretions are increased even in the period without attacks [21]. Several experimental studies showed that several cytokines such as TNF-a, IL-1b, and IL-6, besides playing an important role in allergic disease [22], also have a critical role in damaged cochlea.…”
Section: Discussionmentioning
confidence: 99%
“…However, it is believed that the presence of these inflammatory cytokines in cochlear fluid together with monocytes and macrophages can cause cochlear damage [23,24]. FMF patients are exposed to intensive cytokine secretion and inflammation both during an attack and in the attack-free period, inducing in this way hearing loss [21], but further studies are required on this subject.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation